Exposure to Bleomycin, Etoposide, and Cis-Platinum Alters Rat Sperm Chromatin Integrity and Sperm Head Protein Profile - Maselli, Jennifer (Biol Reprod, 2012)
Testicular cancer, currently the most common cancer affecting men of reproductive age, is one of the most curable malignancies due to the progress made in the early diagnosis and effective treatment of this disease. The coadministration of bleomycin, etoposide, and cis-platinum (BEP) has brought the 5-yr survival rate of testis cancer patients to over 90%. However, this treatment results in reproductive chemotoxic effects. We assessed the effect of BEP treatment on sperm chromatin integrity and sperm head protein profiles of adult male Brown Norway rats following 9 wk of treatment with BEP and in animals treated for 9 wk and then subjected to a 9-wk recovery period. Both the susceptibility of DNA to denaturation and the number of strand breaks were significantly increased in mature sperm following 9 wk of treatment with BEP; proteomic analysis revealed that the expression of several proteins, including HSP90AA1 and HSP90B1, was markedly affected. Following a 9-wk recovery period, mature sperm did not show significant DNA damage, indicating that repair had potentially occurred. Interestingly, the protamination level of the sperm of these animals was significantly decreased, while histones HIST1H1D (H1.2), HIST1H4B (H4), HIST2H2AA3 (H2A1), and HIST1H2BA (H2B1A) were concomitantly up-regulated; this was not observed in the sperm immediately following 9 wk of treatment. Thus, there are persistent effects on proteins in sperm heads from the cauda epididymidis 9 wk posttreatment, in the absence of DNA strand breaks. We suggest that these effects on the sperm head proteome may contribute to long-lasting adverse effects in the progeny of BEP-exposed males.